Kashmir Tourism – An Unexplored Economic Goldmine - Zahid Masroor; Dr. Ramachandran, (International Journal of Management Studies (IJMS), 2021)
Every country has a set of states that contribute to its economy in a unique way depending upon their natural resources, infrastructure, geology and an array of other factors. In this research paper, Kashmir the northern most Indian state is under consideration. The beautiful landscape of Kashmir, its lakes and other natural features give it a tremendous tourism potential given the right destination marketing. Contemporary poets have compared the state to paradise and has a rich heritage associated with it. Given the multi-dimensional tourism aspects, the state is still lingering economically. Where do the flaws lie, is it all because of the tense political situation or is there something more to it? It is true that the political unrest is responsible for the tourism lag but is it only that and the answer is NO. The factors that affect its tourism in the positive ways and the factors that affect it negatively will be studied in this paper and a logical conclusion will be interpreted to help the state improve its tourism and boost its economy.